2011
DOI: 10.1063/1.3530434
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure cold plasma as an antifungal therapy

Abstract: A microhollow cathode based, direct-current, atmospheric pressure, He/O2 (2%) cold plasma microjet was used to inactive antifungal resistants Candida albicans, Candida krusei, and Candida glabrata in air and in water. Effective inactivation (>90%) was achieved in 10 min in air and 1 min in water. Antifungal susceptibility tests showed drastic reduction of the minimum inhibitory concentration after plasma treatment. The inactivation was attributed to the reactive oxygen species generated in plasma or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…Morfill et al report the same 4 log reductions with a treatment of only 5 s for a "barrier corona discharge" [115]. Notably, the inactivation of different Candida strains (although not biofilms) with a plasma jet was reported recently by Sun et al [80]. The device and treatment protocol was also used by Feng et al [79] and is based on the same design used in our study [49].…”
Section: Introductionsupporting
confidence: 60%
“…Morfill et al report the same 4 log reductions with a treatment of only 5 s for a "barrier corona discharge" [115]. Notably, the inactivation of different Candida strains (although not biofilms) with a plasma jet was reported recently by Sun et al [80]. The device and treatment protocol was also used by Feng et al [79] and is based on the same design used in our study [49].…”
Section: Introductionsupporting
confidence: 60%
“…Although a few studies have reported the successful treatment of dental microorganism in root canal cavity [8,12], the fungi biofilms are still a big challenge in clinical therapy. In our previous study, successful treatment 10 strains of Candida biofilms (4 strains of Candida albicans, 3 strains of Candida glabrata, and 3 strains of Candida krusei) in vitro were demonstrated within 1 min's treatment [25,28]. However, it is important to realize the complex of the environment can compromise the efficiency of the therapy [29].…”
Section: Discussionmentioning
confidence: 94%
“…Tim Maisch et al [27] found that plasma at room temperature can lead to an 3 * 5 log 10 reduction on 24-h Candida albicans biofilms formed on 6-well plates, which is comparable to 70 % ethanol treatment. Successful treatment of Candida albicans by cold He/O 2 plasma has been demonstrated both in petri dish and liquid environment [25,28]. However, it is crucial to understand the complexity of the biofilm microenvironment on PMMA may compromise the efficiency of the therapy [29].…”
Section: Introductionmentioning
confidence: 99%
“…36.9 ) [1][2][3]16 ] . The effects of electromagnetic fi elds on biological objects are still insuffi ciently studied.…”
Section: Fungicidal Effect Of Plasma and Radio-wave Treatmentmentioning
confidence: 98%